Long‐Term Dynamics in "Trophy" Sizes of Pelagic and Coastal Pelagic Fishes among California Recreational Fisheries (1966–2013). Issue 5 (3rd August 2016) - Bellquist, Lyall F.; Graham, Jeffrey B.; Barker, Amanda; Ho, Jason; Semmens, Brice X.
Abstract: In California, recreational fisheries contribute a significant amount to coastal economies, with pelagic and coastal pelagic species constituting a principal set of target species during summer and fall. Although traditional catch frequency (landings) data sets exist for these species, size‐specific information is limited, especially for the largest size‐classes. We digitized weekly records of trophy catch reported in the "Whoppers of the Week" section of the Western Outdoor News, a California fishing and hunting newspaper published since 1953. The resulting database contained catch records that described the largest fish caught at each sportfishing landing site along the California coast during 1966–2013. We then assessed the temporal dynamics in trophy size of the top‐15 pelagic and coastal pelagic species, with a combined total of 21, 440 individual catch records. Among the 15 pelagic and coastal pelagic species examined, the Yellowfin Tuna Thunnus albacares and Striped Bass Morone saxatilis were the only species that showed clear long‐term declines in trophy size over the study period, whereas the Pacific Bluefin Tuna Thunnus orientalis, White Seabass Atractoscion nobilis, and Yellowtail Jack Seriola lalandi exhibited long‐term increases in size. In general, the trophy sizes of pelagic species were more variable than those of coastal pelagic species and were not as consistently correlated with oceanographic conditions; both findings likely reflect the fact that oceanography drives the availability but not necessarily the size of pelagic species catch. In contrast, coastal pelagic species demonstrated trends in trophy sizes that were more consistently responsive to both oceanography and fisheries management. Our results suggest that oceanographic processes, natural history characteristics, fishing, and fisheries regulations each play a role in trophy size dynamics, but their relative influences vary among species. Received December 12, 2015; accepted April 26, 2016Published online August 3, 2016